IMPLEMENTATION OF THE SIMPLE ADDITIVE WEIGHTING METHOD FOR EMPLOYEE PERFORMANCE ASSESSMENT - Siti Aisyah (Jurnal Riset Informatika, 2021)
In the process of evaluating employee performance, the company has established standard operating procedures. Of the many standards, it is difficult for management to give weight to each standard. Therefore, a decision-making system is needed to improve company performance and productivity. Human resources must be able to improve employee performance. Professional knowledge or ability. The current appraisal problem, including the employee performance appraisal process, is still using the traditional and not yet accurate method. The research was conducted using the simple additive weighting (SAW) method. The results of this study indicate that by using the SAW method, management is more likely to pay attention to employee performance evaluation, and is more organized and efficient in evaluating employee performance.